The performance of emerging markets during the fed's easing and tightening cycles: A resilience analysis across economies - Joshua Aizenman; Donghyun Park; Irfan A. Qureshi; Jamel Saadaoui; Mohammed Gazi Salah Uddin (Asian Development Bank (ADB), 2024)
We investigate the determinants of the performance of emerging markets (EMs) during five United States (US) Federal Reserve monetary tightening and easing cycles from 2004 to 2023. We study how macroeconomic and institutional conditions of an EM at the beginning of a cycle explain EM resilience during each cycle. More specifically, our baseline cross-sectional regressions examine how those conditions affect three measures of resilience: bilateral exchange rate against the US dollar, exchange rate market pressure, and economy-specific Morgan Stanley Capital International (MSCI) index. We then stack the five cross-sections to build a panel database to investigate potential asymmetry between tightening versus easing cycles. Our evidence indicates that macroeconomic and institutional variables are associated with EM performance, determinants of resilience differ during tightening versus easing cycles, and institutions matter more during difficult times. Our specific findings are largely consistent with economic intuition. For instance, we find that current account balance, international reserves, and inflation are all important determinants of EM resilience.
Keywords: E58; 330; monetary policy cycle; emerging markets; resilience; macroeconomic fundamentals; Federal Reserve